Circus stories in basic vocabulary - Dolch, Edward William 1889-1961 (The Basic vocabulary series, 1956)
Eighteen stories, based on true episodes, about the people and animals in a circus, such as the first woman trapeze artist to do the triple somersault, and the elephant who stole lemonade.